Influence of Hybrid Woven Fabric Parameters on Shielding Effectiveness - Jacek Leśnikowski; Magdalena Tokarska (Journal of Natural Fibers)
Hybrid fabrics composed of wool and silver-metalized yarns were objects of interest as materials for electromagnetic shielding applications. They can be used where electromagnetic radiation levels, to some extent, exceed the permissible values. However, the shields made from these fabrics offer greater comfort to the user than those made from metalized fabrics. The influence of the hybrid fabric weave, silver-metalized yarn density, yarn fraction, and electrical properties, as well as the thickness of the fabric, surface mass, and apparent density on the shielding effectiveness, was investigated. The statistical analysis showed that the weave of the tested fabrics has a statistically significant impact on their shielding effectiveness. For plain weave fabrics, the shielding effectiveness value is 11 dB and 14 dB for low and high frequencies, respectively. For twill weave fabrics, the shielding effectiveness value is 15 dB and 14 dB for low and high frequencies, respectively. The shielding effectiveness of sateen wool fabrics decreased from 33 dB for low frequency to 12 dB for high frequency. The fabric sheet resistivity, resulting from the fraction of electroconductive yarn in the non-conductive textile material, also significantly affects the material’s ability to shield.